PENGARUH PROMOSI IKLAN SHOPEE PADA SAAT PANDEMI COVID-19 TERHADAP PERULAKU KONSUMTIF : Studi Kepada Pengunjung Shopee Dengan Karakteristik Mahasiswa - Rizqulloh Diandra Azni (2021)
The COVID-19 pandemic has had a negative impact on all kinds of aspects, one of which is the economy. The impact is a decrease in people's purchasing power and also affects Shopee, which is a well-known e-commerce in Southeast Asia. As a result of this, Shopee spreads a promotional campaign with the aim of increasing people's purchasing power again through an advertisement. The public's response to the advertisement promotion is of various kinds and in this study the researcher will be associated with students, because students have characteristics that follow technological developments and students are very easy to consumptive behavior. The purpose of this study was to determine whether there was an effect of Shopee Advertising promotion during the COVID-19 pandemic on consumptive behavior. The method that the researcher uses here is the Quantitative Method. The results of this study are the results of the Correlation Test of Variable X (Advertising Promotion) and Variable Y (Consumptive Behavior) showing a correlation of 0.728. The results of the T/Hypothesis Test of 10,513 means that Ho is rejected and Ha is accepted. The conclusion is that there is an influence between Shopee promotions during the COVID-19 Pandemic Period on student consumptive behavior, from the results of the Determinant Coefficient Test calculation of 53% while the remaining 47% is influenced by other factors outside the study. Keywords : Promotion, COVID-19 Pandemic, Advertising, Consumptive Behavior